Karakterisasi Komposit Serat Pelepah Pisang dan Serbuk Cangkang Kelapa Sawit - Jumatul Annisa; Dwi Puryanti; Sri Handani (Jurnal Fisika Unand, 2026)
Research on themanufacture of composites reinforced with banana stem fiber and palm kernel shells aims to analyze the effect of variation in the volume fractionof banana stem fiber and palm kernel shells on the mechanical and physical properties of the composite. The composite was fabricated using the hand lay-up method with volume fraction variations (matrix: fiber: shell) of 40%:50%:10%, 40%:40%:20%, 40%:30%:30%, 40%:20%:40%, and 40%:10%:50%. Mechanical test include Charpy impact test, compressive strength test using a Universal Testing Machine (UTM),Vickers hardness test, and water absorption test. The results showed that the highest impact strength of 0,0947 J/mm2 was obtained at 40%:20%:40% composition, the highest compressive strength of 7,69 MPa at 40%:50%:10%, and the highest hardness value of 18,68 HV at 40%:40%:20%. The lowest water absorption value of 14,28% at 40%:10%:50%. These result indicate that the composition of 40%:20%:40% is the optimum composition for automotive dashboard applications, as it meets the mechanical standards required for dashboard materials.